Analisis Kurikulum Kampus Merdeka Episode 14: Strategi Pemberdayaan Perguruan Tinggi dalam Pencegahan Kekerasan Seksual - Adzibah, Salsabila I’tilaful; Adzillah, Salsabila Nur Imatul; Atika, Atika (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2025)
This study aims to evaluate the implementation of the 14th episode of the Merdeka Campus Curriculum policy in preventing sexual violence at Islamic religious higher education institutions in Indonesia. Using a qualitative approach through literature reviews and in-depth interviews, the study identifies key challenges in policy implementation, including a lack of socialization, insufficient trained human resources, and cultural resistance. The findings indicate that while the policy provides a solid foundation for creating safe campus environments, its implementation requires significant improvements. Education based on moral values, strengthening specialized service units, and engaging all campus stakeholders are the primary recommendations. This research is expected to contribute practical insights toward fostering a more inclusive and responsive campus environment regarding sexual violence issues.